The effect of silymarin on ischemia-reperfusion injury in skeletal muscles of rats - Abdullah Ozer; Basak Kocak; Mustafa Arslan; Baris Mardin; Aysegul Kucuk; Saban Cem Sezen; Mustafa Hakan Zor; Mustafa Kavutcu (Turkish Journal of Vascular Surgery)
Aim: Although the precise process is not entirely elucidated, it is well-known that oxidative stress mediators contribute to ischemia-reperfusion (I/R) injury. The impact of silymarin on I/R injury in many different tissues has been examined. For this purpose, we planned to see the effect of silymarin on muscle tissue in rats subjected to lower extremity I/R injury. Material and Methods: We used 18 male Wistar albino rats weighing 225-275 g. Each of the three groups of rats [Control (C), Ischemia-Reperfusion (I/R), and Silymarin-Ischemia/Reperfusion (S-I/R)] consisted of six rats. Silymarin was administered intraperitoneally 30 minutes before the procedure. (100 mg/kg-1) In Group I/R, the infrarenal abdominal aorta was clamped with a microvascular clamp. The clamp was removed after 120 minutes, and reperfusion was achieved for the next 120 minutes. At the end of the reperfusion period, muscle tissue samples were collected, and Malondialdehyde (MDA), catalase (CAT) enzyme activity levels and histopathological parameters were compared. Results: In the histopathological examination, no degeneration was observed in the muscle fibers in the Group C, while findings of striated muscle damage such as muscle atrophy/hypertrophy, muscle degeneration/congestion, internalization of the muscle nucleus/oval/central nucleus, fragmentation/hyalinization and leukocyte cell infiltration were seen in the Group I/R. In Group S-I/R, muscle atrophy /hypertrophy, internalization of the muscle nucleus/oval/central nucleus, fragmentation/hyalinization, and leukocyte cell infiltration were observed to improve these damaged areas compared to Group I/R. MDA levels in the Group I/R were significantly higher compared to Group C and S-I/R. The activity of the CAT enzyme was much higher in Group I/R compared to Group C. Conclusion: Our study revealed that 100 mg/kg-1 silymarin administered by intraperitoneal injection 30 minutes before ischemia effectively decreased lipid peroxidation, oxidative stress, and the injury caused by I/R in muscle histology in rats. [Turk J Vasc Surg 2024; 33(3.000): 171-5]